Linking the commons and climate change to collective actions - Shaleh, Adha (2025)
This article discusses the commons and collective actions and three levels in collection actions: macro, micro, and supra socio-ecological aspects in governing the commons. In doing so, it asks how societies continue to build climate adaptation and mitigation strategies. The analysis reveals three important points to answer the critical question facing social institutions when dealing with climate related issues. First, the centrality of the community in resource conservation. Second, the importance of well-defined property arrangements to enhance collaborations between states and communities. Third, the notion in community heterogeneity and the variations in perspectives are critical in collective actions. It concedes to the fact that collective actions come to the fore through the organization of social institutional networks that span from multiple layers in society. This point acknowledges the importance of community and cooperation in resource management, including in the inclusiveness of local communities, states, private sectors, and citizens. The article concludes with two recommendations to policy makers: (A) Reviving social capital in the climate change discourse and (B) Good governance, as the world governments face climate challenges and the urgent need for the organisation of social institutions to deal with the inherent complexities in the commons, climate change and collective actions.